Prototype of Interest Measurement Expert System and Career Field Based on Holland Theory in Indonesia - Sutomo, Rudi; Sudirgo, Victor Angkawijaya (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
This research intends to develop an application based on an expert system that aids in assisting a person in identifying the type of employment that best fits their personality and set of traits. When a task that was previously performed manually and will be transferred to a computer system based on an expert system, measurements are made of each person's interests and talents. The Visual Basic programming language was used to construct this application. Realistic, Investigative, Artistic, Social, Enterprising, Conventional (RIASEC), developed based on Holland's thesis, is one of the six fundamental personalities that must be considered to suit individual psychological conditions in professional growth. The six parameters will be provided in various question formats, including graphic images, to help with measurement accuracy. Measurements are improved in accuracy and efficiency thanks to this application. It is anticipated that the system will be able to replace the psychologist in gauging interest according to Holland's theory if adequate measurement and analysis findings are available.